Models for evaluating territorial competitiveness - Mihai Alexandru Chitea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The present study aims to highlight the main models for evaluating territorial competitiveness used at international and European level starting from the following premise: despite the difficulties encountered in the process of defining and understanding the competitiveness term and of numerous and different scientific approaches, there are, though, common elements that can be found at the level of the majority of models for evaluating national, regional and local competitiveness. The paper turns to bibliographic study and comparative analysis, highlighting the main theoretical approaches of competitiveness and the models developed on their basis. Although the indices used within the models present certain specific characteristics derived from the theoretical approach on which it is based, but also implied by the selected aggregation level, there are several central elements that can be found at the level o the majority of evaluation models such as: economic performances, investments level, institutions, infrastructure, education, health and population's welfare.
Keywords: 330; territorial; regional competitiveness; evaluation models; indices